Black Beauty, the autobiography of a horse - Sewell, Anna, 1820-1878.; Dennis, Wesley (Cleveland, New York, World Pub. Co., 1946)
A nineteenth-century English horse tells his life story--describing his many experiences and masters, both good and bad.
13
Keywords: Horses -- Fiction; Horses -- Juvenile fiction